2017
DOI: 10.1161/circulationaha.117.028981
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Similarities in Atrial Fibrillation Epidemiology, Risk Factors, and Mortality in Community Cohorts

Abstract: BACKGROUND:Atrial fibrillation (AF) is a common cardiac disease in aging populations with high comorbidity and mortality. Sex differences in AF epidemiology are insufficiently understood. METHODS:In N=79 793 individuals without AF diagnosis at baseline (median age, 49.6 years; age range, 24.1-97.6 years; 51.7% women) from 4 community-based European studies (FINRISK, DanMONICA, Molisani Northern Sweden) of the BiomarCaRE consortium (Biomarker for Cardiovascular Risk Assessment in Europe), we examined AF inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
223
6
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 340 publications
(263 citation statements)
references
References 52 publications
8
223
6
9
Order By: Relevance
“…Recent results from a substudy of the Biomarcare Consortium involving data from 4 community‐based European studies (FINRISK [Finnish National Risk Factor Survey], DanMONICA [Danish Monitoring of Trends and Determinants in Cardiovascular Disease], Moli‐sani, and Northern Sweden), including data from 79 793 individuals, found that among the classic risk factors, BMI explained the largest proportion of AF risk. Sex differences were seen for risk associations of BMI (HR per SD increase was 1.18 [95% CI, 1.12–1.23] in women versus 1.31 [95% CI, 1.25–1.38] in men; interaction P =0.001) . Therefore, the current study adds to the body of knowledge by comprehensively determining sex differences in the impact of BMI on future incident AF (including providing BMI‐specific HRs) and confirms that associations between BMI and future development of AF are significant in both sexes but differ in size.…”
Section: Discussionsupporting
confidence: 69%
“…Recent results from a substudy of the Biomarcare Consortium involving data from 4 community‐based European studies (FINRISK [Finnish National Risk Factor Survey], DanMONICA [Danish Monitoring of Trends and Determinants in Cardiovascular Disease], Moli‐sani, and Northern Sweden), including data from 79 793 individuals, found that among the classic risk factors, BMI explained the largest proportion of AF risk. Sex differences were seen for risk associations of BMI (HR per SD increase was 1.18 [95% CI, 1.12–1.23] in women versus 1.31 [95% CI, 1.25–1.38] in men; interaction P =0.001) . Therefore, the current study adds to the body of knowledge by comprehensively determining sex differences in the impact of BMI on future incident AF (including providing BMI‐specific HRs) and confirms that associations between BMI and future development of AF are significant in both sexes but differ in size.…”
Section: Discussionsupporting
confidence: 69%
“…Epidemiological studies show a high lifetime risk of AF in both women and men (4,9). At age 55 years, the lifetime risk to develop AF was 22.2% in women and 23.8% in men in the population-based Rotterdam Study (4).…”
Section: Incidence and Prevalence Of Atrial Fibrillationmentioning
confidence: 99%
“…Obesity has been shown to increase the risk of developing AF by 49% compared to non-obese individuals (10). In the large BiomarCaRE Consortium comprising almost 80,000 individuals among whom over 4,000 incident AF cases, BMI explained the largest proportion of AF risk (around 20% for overweight and obesity combined) (9). Elevated BMI was reported to account for up to 18% of risk for incident AF among women in the Women's Health Study (WHS) (11).…”
Section: Elevated Bmimentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial fibrillation (AF) is the most common cardiac arrhythmia and is highly prevalent in patients with heart failure . The co‐existence of these conditions can be expected by virtue of their prevalence alone: the lifetime risk of developing AF is about one in three in individuals of European ancestry and one in five in individuals of African ancestry, and after age 45 the lifetime risk of heart failure ranges between 20–45%…”
Section: Introductionmentioning
confidence: 99%